An MLP-based Skew Angle Mitigation Method for Bit-Patterned Magnetic Recording - Santi Koonkarnkhai; Kittipon Kankhunthod; Piya Kovintavewat (My University, 2024)
Skew angle (SA) is one of the crucial problems in a bit-patterned magnetic recording (BPMR) system. Practically, during the read process, the read head may be tilted up to 30 degrees (°) away from the target track. Without the SA detection and correction mechanism, the performance of the BPMR system will be unbearable. This paper proposes a SA mitigation strategy for a BPMR system based on a multilayer perceptron (MLP) so as to estimate and rectify the SA. Specifically, the MLP-based SA estimator extracts the SA amount directly from the readback signal, which will then be used in the MLP-based detector to produce the estimated recording bits. Simulation results show that the proposed method can estimate the SA embedded in the readback signal more precisely than the conventional one, which just uses a look-up table to detect the SA from the target coefficients. Particularly, for the system operating at an areal density (AD) of 3 terabits per square inch with SA =15° and 30°, the suggested system performs better than the system without the SA mitigation method.
Keywords: SIGNAL (programming language); Patterned media; Magnetic properties of thin films